Puerperal gravid state in pulmonary tuberculosis undergoing surgery before pregnancy and obstetric care in fifteen patients tisiológico - Migone, Oscar (2015)
In tuberculous subject to surgical operations, but not cured by surgery, similar to very advanced tuberculosis obstetric characteristics are observed; and if cured by operation similar to feature all cured tuberculosis. This behavior depends on factors related to the general condition, muscle tone of the genital tract and probably the early humoral blood clotting process. Lung disease, the patient continues to get pregnant as appropriate, seen the course in severe tuberculosis (high percentage of unfavorable developments) or in the seemingly cured tuberculosis (high percentage of recovery). The pre-pregnancy pulmonary surgery, when it failed to cure, introduced an important variant: increasing unfavorable percentages. There were no maternal deaths.